Defining requirements to develop information security concept n hybrid threats conditions. PART 4 - Гайдур, Галина; Борсуковский, Юрий (SWorldJournal, 2021)
The article considers the basic elements of the formation of separate sections of the concept of information security of business structures and government organizations. The article provides the further requirements for the definition of further componen